2012
DOI: 10.1159/000342619
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Daily Fluoride Mouth Rinsing on Enamel Erosive/Abrasive Wear in situ

Abstract: It is not known whether application of fluoride agents on enamel results in lasting resistance to erosive/abrasive wear. We investigated if one daily mouth rinse with sodium fluoride (NaF), stannous fluoride (SnF2) or titanium tetrafluoride (TiF4) solutions protected enamel against erosive/abrasive wear in situ (a paired, randomised and blind study). Sixteen molars were cut into 4 specimens, each with one amalgam filling (measurement reference surface). Two teeth (2 × 4 specimens) were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 58 publications
2
32
1
3
Order By: Relevance
“…Hove et al [2008] tested different fluoride solutions (1.5% TiF 4 ; 3.9% SnF 2 ; 2.1% NaF; all solutions contained 0.5 mol/l F) in an in situ erosion-only model and found that the TiF 4 and the SnF 2 both formed a protective surface layer on enamel, and both showed significant protection against erosion in comparison to the NaF solution and to placebo (no fluoride treatment); however, the authors did not observe any significant differences between TiF 4 and SnF 2 . Similarly, in the in situ erosion-abrasion study by Stenhagen et al [2013], the protective layer on enamel had an average thickness of 0.6 μm for TiF 4 and of 1.0 μm for SnF 2 , and the TiF 4 and SnF 2 solutions led to a reduction in enamel erosive-abrasive wear of 90 and 94%, respectively. The authors also reported no significant differences between the protective effect of TiF 4 and SnF 2 solutions.…”
Section: Products Containing Titanium Ionsmentioning
confidence: 83%
See 1 more Smart Citation
“…Hove et al [2008] tested different fluoride solutions (1.5% TiF 4 ; 3.9% SnF 2 ; 2.1% NaF; all solutions contained 0.5 mol/l F) in an in situ erosion-only model and found that the TiF 4 and the SnF 2 both formed a protective surface layer on enamel, and both showed significant protection against erosion in comparison to the NaF solution and to placebo (no fluoride treatment); however, the authors did not observe any significant differences between TiF 4 and SnF 2 . Similarly, in the in situ erosion-abrasion study by Stenhagen et al [2013], the protective layer on enamel had an average thickness of 0.6 μm for TiF 4 and of 1.0 μm for SnF 2 , and the TiF 4 and SnF 2 solutions led to a reduction in enamel erosive-abrasive wear of 90 and 94%, respectively. The authors also reported no significant differences between the protective effect of TiF 4 and SnF 2 solutions.…”
Section: Products Containing Titanium Ionsmentioning
confidence: 83%
“…Although the authors clearly observed the formation of a layer on the enamel surface after the use of TiF 4 solution, they concluded that the solution was not able to prevent erosion. Some in situ [Hove et al, 2008;Stenhagen et al, 2013] and in vivo [Hjortsjo et al, 2009] studies have compared both TiF 4 and tin-containing products. Hove et al [2008] tested different fluoride solutions (1.5% TiF 4 ; 3.9% SnF 2 ; 2.1% NaF; all solutions contained 0.5 mol/l F) in an in situ erosion-only model and found that the TiF 4 and the SnF 2 both formed a protective surface layer on enamel, and both showed significant protection against erosion in comparison to the NaF solution and to placebo (no fluoride treatment); however, the authors did not observe any significant differences between TiF 4 and SnF 2 .…”
Section: Products Containing Titanium Ionsmentioning
confidence: 99%
“…The intricate interplay among these factors is important to consider when attempting to explain why some individuals tend to develop more erosive lesions than others, despite exposure to the same intensity of acidic challenges [Lussi, 2006]. In recent in situ studies, it was observed that human enamel etched differently [Hove et al, 2008;Stenhagen et al, 2013;Hove et al, 2014;Hystad Hove et al, 2015]. However, the results did not reveal whether this was due to variations in the oral environment or in the enamel composition.…”
mentioning
confidence: 99%
“…The low pH might also contribute to the higher precipitation of TiF 4 deposits. The thickness of the protective layer formed by fluoride compounds and post-erosion enamel loss were also evaluated by Stenhagen et al 29 The average thickness of the glaze-like layer formed by TiF 4 was 600 nm, 29 but a TiF 4 solution was used. Since TiF 4 formulations and methodologies differed between the two studies, the results cannot be directly compared.…”
Section: Discussionmentioning
confidence: 99%